Performance Analysis of Civil Servants in Kampar District Government: Overview from the Perspective of Work Ethics and Compensation - Aras Aira; Wenny Desty Febrian (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine and examine the effect of work ethics and compensation on employee performance. This research was conducted at the offices in Kampar district, the offices in Kampar district totaled 21 offices. The population in this study was the entire number of civil servants in Kampar district, amounting to 969 people, while the sample was random sampling, the sample was taken 10% of the population, so the sample in this study was 97 people. Analysis of the data used in this study is to test the quality of the data consisting of validity and reliability tests. Classical assumption testing using normality, multicollinearity and heteroscedasticity, while for hypothesis testing using multiple regression test. Data processing in this study using SPSS version 20.0. The results of data processing on the hypothesis indicate that work ethics has a positive and significant influence on employee performance, so it can be concluded that hypothesis 1 is accepted. While the second hypothesis, the results of data processing indicate that compensation has a significant positive effect on employee performance, so it can be concluded that the second hypothesis is accepted. The results of R2 show that the contribution of work ethics and compensation on employee performance is 41.5%.